Quranic memorization instruction for children with disabilities in Ainul Yakin Inclusive Islamic Boarding School - Sarwadi; Eko Ngabdul Shodikin (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
People with disabilities have the same rights as other children in all aspects of life. This includes education, where they have the right to attend school to receive education and instruction, including religious education such as memorizing the Quran. However, teaching the Quranic memorization, which requires a strong level of concentration and memory, to people with disabilities has its challenges. This has prompted researchers to study the implementation of Quranic memorization instruction for people with disabilities more deeply. This qualitative research study used participant action research to answer research questions, with quantitative methods in the form of descriptive analysis and interpretation. The research found that children with intellectual disabilities learn new things more slowly compared to their peers. The Quranic memorization approach for children with intellectual disabilities should focus on individualized instruction. Due to their below-average IQ, these children cannot be forced to understand or comprehend material quickly. Therefore, teachers should not delve too deeply into the material, as this may be too difficult for children with intellectual disabilities. It is necessary to develop a variety of teaching methods for children with intellectual disabilities because of their limitations in mental intelligence.